2013
DOI: 10.1007/s00520-013-2088-9
|View full text |Cite
|
Sign up to set email alerts
|

The end-of-life phase of high-grade glioma patients: a systematic review

Abstract: The EOL phase of HGG is substantially different from other patient groups, and more clinical studies in HGG on supportive medication, advance care planning and decision making are required. The organization of care, development of guidelines and interventions to decrease caregiver burden in the EOL phase are critical as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 48 publications
2
56
0
1
Order By: Relevance
“…Substantial loss of independence commonly occurs with the progression of brain cancer 29 . Studies have shown that brain cancer produces a high degree of symptom burden for patients and caregivers 36,37 , with caregivers reporting poor physical and emotional health, career sacrifices, monetary losses, and immense strain 36,37 . Currently, the provision of support and coping therapy for informal carers is lacking, and that lack in turn contributes to a worsening of their stresses 34,36,38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Substantial loss of independence commonly occurs with the progression of brain cancer 29 . Studies have shown that brain cancer produces a high degree of symptom burden for patients and caregivers 36,37 , with caregivers reporting poor physical and emotional health, career sacrifices, monetary losses, and immense strain 36,37 . Currently, the provision of support and coping therapy for informal carers is lacking, and that lack in turn contributes to a worsening of their stresses 34,36,38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…The combination of motor dysfunction, seizures, cognitive deficits and, finally, loss of consciousness, together with gradual impairments in communication and loss of independence in HGG patients differs from other types of cancer and necessitates multidimensional and targeted care in the EOL phase of these patients [3,4,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Although the length of the EOL phase in individual cases ranges from days to weeks prior to death, in our definition, it starts when further tumor directed treatment is no longer an option, which generally is no earlier than 3 months (mo) before death. During this phase, where symptoms further deteriorate and disability increases, care is primarily aimed at optimizing quality of life [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, no definition of the EOL phase exist, therefore, in this guideline we refer to the EOL phase as the last three months of life. 4 Given the growing awareness for PC in glioma patients and despite the limited evidence from clinical studies on PC, and more specifically on PC in the EOL phase in glioma, a systematic literature review was performed by the European Association of Neuro-Oncology (EANO) palliative care task force to identify all relevant literature on PC in primary brain tumours.…”
Section: Introductionmentioning
confidence: 99%